Association of periodontitis and tooth loss with extent of coronary atherosclerosis in patients with type 2 diabetes mellitus - Shen, Minhua; Li, Zhen; Li, Huizhi; Yan, Xinfeng; Feng, Bo; Xu, Lei (Frontiers in Endocrinology, 2023)
Aim The objective was to investigate the association of periodontitis and tooth loss with extent of diabetic coronary atherosclerosis. Materials and methods 272 patients who were hospitalized at Shanghai East hospital and underwent a coronary artery calcium (CAC) CT scan were enrolled in this study. Individuals were grouped based on their CAC scores into a normal-to-mild coronary atherosclerosis (AS) group (0 ≤ score ≤ 100, n=184) and a moderate-to-severe group (score≥101, n=88). Periodontitis parameters and number of missing teeth were evaluated for every patient. The severity of periodontitis was categorized as mild, moderate, or severe. The taxonomic composition of the microbiota was determined using full-length 16S ribosomal RNA gene sequencing. Salivary inflammatory factors were tested by ELISA. Results Clinical attachment loss (CAL) (P =0.05) and the number of teeth lost (P = 0.016) were significantly higher in the moderate-to-severe coronary AS group, with these differences being more obvious in younger patients and patients with short-duration diabetes. Multivariate logistic regression analysis revealed that CAL (OR = 1.231, 95% CI = 1.066–1.214, P = 0.047) and having 10–19 missing teeth (OR = 1.604, 95% CI = 1.393–6.555, P = 0.05) were strongly associated with the presence of moderate-to-severe coronary AS. Salivary IL-6 and TNF-α levels, as well as levels of Porphyromonas gingivalis and Neisseria mucosa, were significantly elevated in the moderate-to-severe coronary AS group. Conclusion It was found that both tooth loss and CAL were related to the extent of diabetic coronary AS. Saliva inflammatory factors and oral bacteremia may be new biomarkers for moderate-to-severe coronary AS.